Adaptive BIM–IDS Framework for Semantic-Level Data Interoperability in Construction 5.0 Environments - Mariana García; Lasarus Arintoko (Universitas Sains dan Teknologi Komputer, 2026)
Physical infrastructure further becomes digitalized, but semantic-level interoperability between Building Information Modeling (BIM) and Information Delivery Specification (IDS) is a problem that is preventing one-size-fits-all information exchange. Conceptually, the current study conceives and analyzes an Adaptive BIM–IDS Framework that can extend support toward semantic conjoining within Construction 5.0 environments through ontology-based reasoning, adaptive mapping, and human–machine cooperation. A constructive research and simulation approach was adopted, wherein a Systematic Literature Review was integrated with PRISMA and dummy dataset simulation of BIM–IDS. Ontology-based mapping, SHACL validation, and SPARQL reasoning were adhered to for semantic completeness, logical consistency, and semantic flexibility of the framework. Performance was tested in three replicable tests Context Recognition Accuracy (CRA), Interoperability Consistency Ratio (ICR), and Adaptive Mapping Success Rate (AMSR) that exhibited higher semantic compatibility than a non-semantic control. While results are hypothetical, simulation-based, rather than empirical, the study presents replicable reason pipeline and formalized semantic ontology to support adaptive, ontology-enabled interoperability feasibility. Outcomes guide theoretical foundation of adaptive BIM–IDS integration and drive subsequent empirical application toward semantically harmonized, human-centered Construction 5.0 systems.